2010
DOI: 10.18553/jmcp.2010.16.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Recommendations to Improve the Quality of Diabetes Care: A Randomized Controlled Trial

Abstract: BACKGROUND: Diabetes mellitus continues to result in substantial morbidity and mortality despite receiving much attention from health care providers. Automated clinician reminder systems have been developed to improve adherence to diabetes care guidelines, but these reminder systems do not always provide actionable information and may be unable to detect relevant, subjective patient information that affects clinical decision making. Face-to-face visits with pharmacists, who have knowledge of care guidelines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…These results suggested that early interventions of drug treatment were very important and directly affect the final outcomes in the study. Furthermore, the importance of early intervention also might be used for other chronic diseases, such as diabetes, liver diseases and blood disorders (Kirwin et al, 2010). Foreign study also found that early use of antihypertensive treatment can prevent complications, prolong life, and especially reduce the actual costs when compared with the late use patients with antihypertensive drugs (McCombs et al, 1994;Sokol et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that early interventions of drug treatment were very important and directly affect the final outcomes in the study. Furthermore, the importance of early intervention also might be used for other chronic diseases, such as diabetes, liver diseases and blood disorders (Kirwin et al, 2010). Foreign study also found that early use of antihypertensive treatment can prevent complications, prolong life, and especially reduce the actual costs when compared with the late use patients with antihypertensive drugs (McCombs et al, 1994;Sokol et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, 33 studies (48.5%) [58][59][60]62,65,68,69,71,72,74,76,78,[81][82][83][84]88,[91][92][93][94][95][96][97]99,100,[103][104][105][106][107]119,121 were judged to be at high risk of bias in at least one domain. The domains most commonly at high risk of bias were 'incomplete outcome data addressed' [15 studies 65,68,72,76,78,[81][82][83][84]88,93,94,100,103,105 (22.7%)], 'protected against contamination' [seven studies 60,62,…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…The domains most commonly at high risk of bias were 'incomplete outcome data addressed' [15 studies 65,68,72,76,78,[81][82][83][84]88,93,94,100,103,105 (22.7%)], 'protected against contamination' [seven studies 60,62,96,99,104,107,119 (10.6%)] and 'similar baseline outcome measurements' [five studies 58,69,92,95,106 (7.6%)]. It was possible to judge if a study was free from selective outcome reporting for only 17 studies (25.7%) 58,59,63,64,67,69,72,77,78,83,84,94,96,99,100,121,123 because of a lack of availability of a prospectively published trial registration or protocol. Although studies were rarely judged to be at a high risk of bias for adequate sequence generation and adequate allocation concealment, the methods associated with these domains were frequently poorly reported.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations